2021
DOI: 10.1002/smll.202101233
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing Temperature Tailors Electrical and Electrochemical Properties through Changing Inner Distribution of Graphite/Polymer

Abstract: The rise of 3D printing technology, with fused deposition modeling as one of the simplest and most widely used techniques, has empowered an increasing interest for composite filaments, providing additional functionality to 3D‐printed components. For future applications, like electrochemical energy storage, energy conversion, and sensing, the tuning of the electrochemical properties of the filament and its characterization is of eminent importance to improve the performance of 3D‐printed devices. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 51 publications
(52 reference statements)
0
27
0
Order By: Relevance
“…SPECM is a scanning probe technique for the non-invasive examination of chemical, electrochemical, and photoelectrochemical characteristics with high spatial resolution. , The microscopic image is generated by recording an amperometric current at the SPECM probe, typically a disc-shaped UME dependent on the position . The localization of conductive surfaces on the 3DCu sample was done using the so-called “feedback mode.” In the feedback mode, the oxidation current of the redox-active mediator FcMeOH measured at the UME depends on the conductivity of the sample and the tip-to-substrate distance. , Isolating materials impede the diffusion of the mediator to the UME, resulting in a decreased current, called “negative feedback”. Conductive materials enable the recycling of the mediator, which results in a higher current, indicating positive feedback.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SPECM is a scanning probe technique for the non-invasive examination of chemical, electrochemical, and photoelectrochemical characteristics with high spatial resolution. , The microscopic image is generated by recording an amperometric current at the SPECM probe, typically a disc-shaped UME dependent on the position . The localization of conductive surfaces on the 3DCu sample was done using the so-called “feedback mode.” In the feedback mode, the oxidation current of the redox-active mediator FcMeOH measured at the UME depends on the conductivity of the sample and the tip-to-substrate distance. , Isolating materials impede the diffusion of the mediator to the UME, resulting in a decreased current, called “negative feedback”. Conductive materials enable the recycling of the mediator, which results in a higher current, indicating positive feedback.…”
Section: Resultsmentioning
confidence: 99%
“…The localized (photo)­electrochemical characterization using SPECM was done with a cross-section sample of a 3DCu electrode doped with Al 2 O 3 . The detailed procedure for preparing the cross-section samples is published elsewhere . Briefly, the 3DCu electrode was encapsulated in a two-component epoxy resin using a vacuum impregnation chamber (CITOVAC, Struers Aps).…”
Section: Experimental Section/methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] However, manufacturing composite electrodes using material extrusion process also provides different variables which can influence the conductivity of the printed electrode. [18,19] Printing parameters can have an influence on the structure of the electrode and previous studies have shown that orientation and print layer thickness can have a significant influence on the number of conductive pathways present within the printed conductive electrode. [20,21] Given the importance of manufacturing electrodes with optimal conductivity through material extrusion process, understanding the influence of different parameters on the printed part is critical as this can alter the conductivity of the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…However, manufacturing composite electrodes using material extrusion process also provides different variables which can influence the conductivity of the printed electrode [18,19] . Printing parameters can have an influence on the structure of the electrode and previous studies have shown that orientation and print layer thickness can have a significant influence on the number of conductive pathways present within the printed conductive electrode [20,21] .…”
Section: Introductionmentioning
confidence: 99%